ERRORS IN WORD ORDER AND SUBJECT-VERB AGREEMENT IN THE UNDERGRADUATE THESIS ABSTRACTS - Ika Febrianti; Mashadi Said (INFERENCE: Journal of English Language Teaching, 2022)
The objectives of the research were formulated to find out the errors of word order and the subject-verb agreement made by the English department students at universities in Indonesia in their undergraduate thesis abstracts. The method of the research was qualitative descriptive. The source of data was 35 undergraduate thesis abstracts from 2017 to 2019 year made by the English department students at universities in Indonesia. Technique of data analysis was through collecting data, identifying of errors, classifying of errors, explaining of errors and evaluating of errors. The classification of the errors is based on Surface Taxonomy category. The research findings reveal that the most common error of word order in the surface taxonomy was omission consisting of 76 or 38% errors. Meanwhile, the most error of subject- verb agreement was omission and misformation with 21 or 48,83%.